Stalin Era Intellectuals: Culture and Stalinism - Irina Sandomirskaja (Nordisk Østforum, 2023)
“It is pertinent to ask to what extent certain cultural phenomena and intellectual currents from the Stalin era really were such unique features that can be branded as Stalinist…”. This is the question that motivated the anthology Stalin Era Intellectuals: Culture and Stalinism under review here.